Joint Data Analysis in Nutritional Epidemiology: Identification of Observational Studies and Minimal Requirements. - Pinart, Mariona; Nimptsch, Katharina; Bouwman, Jildau; Dragsted, Lars O; Yang, Chen; De Cock, Nathalie; Lachat, Carl; Perozzi, Giuditta; Canali, Raffaella; Lombardo, Rosario; D'Archivio, Massimo; Guillaume, Michèle; et al. (J Nutr, 2018)
Background: Joint data analysis from multiple nutrition studies may improve the ability to answer complex questions regarding the role of nutritional status and diet in health and disease. Objective: The objective was to identify nutritional observational studies from partners participating in the European Nutritional Phenotype Assessment and Data Sharing Initiative (ENPADASI) Consortium, as well as minimal requirements for joint data analysis. Methods: A predefined template containing information on study design, exposure measurements (dietary intake, alcohol and tobacco consumption, physical activity, sedentary behavior, anthropometric measures, and sociodemographic and health status), main health-related outcomes, and laboratory measurements (traditional and omics biomarkers) was developed and circulated to those European research groups participating in the ENPADASI under the strategic research area of "diet-related chronic diseases." Information about raw data disposition and metadata sharing was requested. A set of minimal requirements was abstracted from the gathered information. Results: Studies (12 cohort, 12 cross-sectional, and 2 case-control) were identified. Two studies recruited children only and the rest recruited adults. All studies included dietary intake data. Twenty studies collected blood samples. Data on traditional biomarkers were available for 20 studies, of which 17 measured lipoproteins, glucose, and insulin and 13 measured inflammatory biomarkers. Metabolomics, proteomics, and genomics or transcriptomics data were available in 5, 3, and 12 studies, respectively. Although the study authors were willing to share metadata, most refused, were hesitant, or had legal or ethical issues related to sharing raw data. Forty-one descriptors of minimal requirements for the study data were identified to facilitate data integration. Conclusions: Combining study data sets will enable sufficiently powered, refined investigations to increase the knowledge and understanding of the relation between food, nutrition, and human health. Furthermore, the minimal requirements for study data may encourage more efficient secondary usage of existing data and provide sufficient information for researchers to draft future multicenter research proposals in nutrition.
Keywords: Adult; Biomarkers; Blood Glucose; Case-Control Studies; Child; Chronic Disease; Cohort Studies; Cross-Sectional Studies; Diet; Epidemiology; Europe; Genomics; Health Status; Humans; Inflammation; Insulin; Life Style; Lipoproteins; Longitudinal Studies; Metabolomics; Nutritional Status; Observational Studies as Topic; Statistics as Topic

Juvenile stroke in combined syndrome of hereditary hemorrhagic telangiectasia and juvenile polyposis. - Mazzucco, Sara; Benini, Luigi; Gallione, Carol; d'Adamo, Pio; Girelli, Domenico (Neurol Sci, 2014)
Keywords: Adult; Arteriovenous Malformations; Brain Ischemia; Chromosomes, Human, Pair 18; Echocardiography, Transesophageal; Embolism, Paradoxical; Embolization, Therapeutic; Epistaxis; Family Health; Humans; Intestinal Polyposis; Intracranial Embolism; Introns; Lod Score; Male; Pulmonary Artery; Smad4 Protein; Telangiectasia, Hereditary Hemorrhagic; Thalamus; Ultrasonography, Doppler, Transcranial

JCV+ Patients with Inflammatory bowel disease show elevated plasma levels of MIG and SCF. - Comar, Manola; Secchiero, Paola; De Lorenzo, Elisa; Martelossi, Stefano; Tommasini, Alberto; Zauli, Giorgio (Inflamm Bowel Dis, 2012)
Keywords: Adolescent; Adult; Chemokine CXCL9; Child; DNA, Viral; Female; Humans; Inflammatory Bowel Diseases; JC Virus; Leukoencephalopathy, Progressive Multifocal; Male; Stem Cell Factor; Young Adult

JCV/BKV and SV40 viral load in lymphoid tissues of young immunocompetent children from an area of north-east Italy. - Comar, Manola; Zanotta, Nunzia; Bovenzi, Massimo; Campello, Cesare (J Med Virol, 2010)
Polyomavirus infection occurring during childhood is followed by a lifelong latency in immunocompetent subjects. The major site of polyomavirus persistence are the uroepithelial cells which leads to oral transmission. It has recently been hypothesized that tonsils could be a possible reservoir. The role of tonsil, adenoid, and peripheral blood mononuclear cells (PBMCs) as possible sites of JCV, BKV, and SV40 latency in young healthy children was assessed. Two hundred fifteen fresh specimens, including 57 tonsil, 80 adenoid, and 78 PBMC samples from 80 immunocompetent children (mean age 4.8 years) were analyzed to determine the viral load by quantitative real-time PCR. The human herpes virus 6 (HHV-6) was tested as a lymphotropic reference virus. Polyomavirus was detected in 5/80 (6.2%) children while HHV-6 infection affected 27/80 children (33.7%) (P < 0.001). SV40 was detected in one adenoid sample, while footprints of BKV were found in one adenoid and three tonsil samples. JCV was never found in all samples. Polyomavirus sequences were not detected in the 78 blood samples. One adenoid and two tonsils from three children (1.4%) were positive for both polyomavirus and HHV-6. Infections were characterized by low replication rates ranging typically from 1 x 10e(2)/5.5 x 10e(4) to 6.8 x 10e(3)/8.5 x 10e(4) viral copies/number of cells. In conclusion, tonsils and adenoids of children could effectively harbor BKV and SV40, although only very few cells proved to be infected. Nevertheless, the low prevalence of polyomavirus, in comparison with the lymphotropic HHV-6, suggests that these tissues are unlikely to be the preferred site of polyomavirus latency, at least in younger children.
Keywords: Adenoids; BK Virus; Carrier State; Child; Child, Preschool; Female; Herpesvirus 6, Human; Humans; Immunocompetence; Italy; JC Virus; Male; Neutrophils; Palatine Tonsil; Polyomavirus Infections; Simian virus 40; Viral Load; Virus Latency